High-strength nano hybrid soluble bridge plug as well as preparation method and application thereof

By using a zinc-based alloy hollow tube with a bridge plug made of nano-carbon nitride and polybenzimidazole/nano-silica composite film, the problems of strength, dissolution time and residue control in ultra-deep well fracturing were solved, achieving efficient and low-cost downhole plugging and dissolution effects.

CN120830475AActive Publication Date: 2025-10-24中国石油集团工程材料研究院有限公司 +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511333983.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-18
Publication Date
2025-10-24
Estimated Expiration
2045-09-18

AI Technical Summary

Technical Problem

Existing bridge plug technology suffers from insufficient compressive strength, poor dissolution time and residue control, and poor sealing performance in ultra-deep well fracturing. Furthermore, its production process is complex and costly, making it difficult to meet the demands for efficient and low-cost operations.

Method used

Using a zinc-based alloy hollow tube as the substrate, the outer layer is coated with a nano carbon nitride film and a polybenzimidazole/nano silica composite film. It is formed in one step by plasma sintering to create an annular groove structure, which enhances sealing and controllable solubility.

Benefits of technology

It achieves high-strength sealing (pressure resistance 700~750MPa), controllable dissolution (dissolution within 4~12 days) and extremely small residue (<0.15mm), reducing production costs and downhole risks, and meeting the needs of ultra-deep well high-pressure fracturing.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of gas adsorbents, and particularly discloses a high-strength nano-hybrid soluble bridge plug as well as a preparation method and application thereof. The bridge plug body comprises a hollow metal tube, and a plurality of annular grooves are formed in the outer surface of the hollow metal tube around the axis of the hollow metal tube; the carbon nitride film middle layer is located on the outer surface of the bridge plug body; the outermost layer of the polybenzimidazole / nano silicon oxide composite film is positioned on the outer surface of the middle layer of the carbon nitride film; the hollow metal tube is made of zinc-based alloy and comprises, by mass, 5%-7% of titanium, 2%-4% of magnesium, 0.5%-2% of bismuth and the balance zinc. The bridge plug disclosed by the invention is high in plugging strength, controllable in dissolution time and suitable for a high-temperature and high-salt or acid environment, the particle size of residues after dissolution is small, the harsh requirements of ultra-deep well fracturing can be met, and the bridge plug is prepared by adopting a one-step forming process, so that the production cost is remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of multi-stage fracturing of oil and gas wells, and specifically discloses a high-strength nano-hybrid soluble bridge plug and a preparation method and application thereof, which is suitable for temporary plugging and controllable dissolution of downhole tools in oil and natural gas extraction. Background Art

[0002] Soluble bridge plugs are a key tool in staged fracturing operations in the oil and gas industry. They are widely used in the development of shale gas, tight oil and gas, and deep oil and gas reservoirs, with growing demand in ultra-deep wells (depths greater than 6,000 meters, pressures greater than 100 MPa, and temperatures between 140 and 160°C). Fracturing operations use bridge plugs to create a temporary seal within the wellbore, enabling stratified production. After the operation is completed, the bridge plug dissolves through corrosion or chemical degradation in the downhole environment (typical conditions: 140-160°C, 10-20% sodium chloride solution, pH 3.5-6.5), eliminating the need for mechanical drilling or recovery, thereby improving operational efficiency and reducing operating costs. In recent years, with the increasing development of unconventional oil and gas, ultra-deep well fracturing has placed higher demands on bridge plugs. Existing bridge plug technologies include traditional non-soluble bridge plugs, aluminum-magnesium alloy soluble bridge plugs, improved aluminum-magnesium alloy, composite bridge plugs and polymer-based bridge plugs. However, these existing bridge plug technologies have significant deficiencies in strength, solubility, residue control, sealing performance and process efficiency, making it difficult to meet the requirements of complex working conditions.

[0003] Traditional non-dissolvable bridge plugs are based on high-strength steel, using 4140 alloy steel containing 0.8-1.1wt% chromium and 0.15-0.25wt% molybdenum, with compressive strength up to 800MPa. The bridge plug is cylindrical, with diameter 50-150mm and length 200-400mm, with a fluororubber or nitrile rubber seal ring embedded on the outside, with thickness 5-15mm. The bridge plug relies on mechanical expansion to adhere to the casing (inner diameter 70-200mm) with a sealing pressure of about 90MPa. The preparation process includes hot rolling or forging the base (temperature 1100-1200℃, pressure 50-80MPa), machining the shape on a CNC lathe, and hot pressing the seal ring (temperature 180-220℃, pressure 5-10MPa). The equipment includes a hot rolling machine and a CNC lathe (e.g. Haas, model TL-2, USA). This technology has been widely used in conventional oil and gas wells since the late 20th century. However, the shortcomings of traditional non-dissolvable bridge plugs have significantly limited their application in modern fracturing operations. First, the steel base and rubber seal ring cannot be dissolved downhole and need to be removed by drilling and grinding, which takes 2-5 days and is inefficient. Second, drilling and grinding generates 1-5mm of metal and rubber fragments, increasing the risk of downhole plugging and requiring additional cleaning, which is costly. Third, the rubber seal ring ages at high temperatures (greater than 150℃) or in acidic environments (pH less than 4), reducing the sealing pressure to less than 70MPa, making it difficult to meet the high pressure requirements of ultra-deep wells. Fourth, the forging and multi-step mechanical processing process is complex, with a long production cycle (2-3h per piece) and high cost. In addition, the drilling and grinding fragments need to be treated on the ground, increasing the environmental burden. These shortcomings indicate that traditional non-dissolvable bridge plugs cannot adapt to efficient and low-cost fracturing operations in ultra-deep wells.

[0004] Aluminum-magnesium alloy soluble bridge plugs are currently the mainstream technology. Their matrix consists of aluminum (80-85 wt%), magnesium (10-15 wt%), and a small amount of zinc, with a grain size of 10-20 μm. These plugs are cylindrical, 50-120 mm in diameter and 100-250 mm in length, with an internal fluid channel (8-15 mm in diameter). Externally, they are sealed with a soluble rubber seal, 5-10 mm thick. Dissolution times range from 7-30 days at a rate of 0.1-2.0 mm / day, compressive strengths of 400-500 MPa, and sealing pressures of approximately 70 MPa. The fabrication process involves vacuum melting the alloy, extruding the matrix, machining the outer shape, and hot-pressing the seal ring. The equipment used includes a vacuum melting furnace and an extruder. While aluminum-magnesium alloy bridge plugs achieve soluble functionality, they also have significant drawbacks. First, their compressive strength is only 400-500 MPa, making them difficult to withstand the high pressures of ultra-deep wells and prone to plastic deformation or fracture. Second, the dissolution time is long, ranging from 7 to 30 days, and the rate fluctuates widely (0.1 to 2.0 mm / day). This is due to the uneven distribution of alloy components and the unstable degradation of polyglycolic acid, which prolongs the operation cycle and increases costs. Third, the particle size of the residue ranges from 0.8 to 1.2 mm, with residues larger than 1 mm easily clogging the wellbore and requiring additional cleaning. Fourth, the seal degrades too rapidly at high temperatures (greater than 150°C) or in acidic environments (pH less than 4), resulting in a sealing pressure below 70 MPa, affecting reliability. These shortcomings limit its application in ultra-deep wells.

[0005] The improved alloy bridge plug attempts to improve performance, the base body uses aluminum magnesium alloy, containing 75-80wt% aluminum, 12-18wt% magnesium, 2-5wt% nickel, and the grain size is 8-15μm. The surface is sprayed with polyether ether ketone coating, the thickness is 20-50 microns, and part of the rubber sealing ring is replaced. The bridge plug diameter is 60-150mm, the length is 120-300mm, the internal passage diameter is 10-20mm, and the surface roughness Ra is 0.4-0.8μm. In the downhole environment, the alloy dissolves by corrosion, the polyether ether ketone coating slowly hydrolyzes, the dissolution time is 7-20 days, the rate is 0.2-1.5mm / d, the compressive strength is 550MPa, and the sealing pressure is about 85MPa. The preparation process includes gas atomization preparation of alloy powder (cooling rate 1000-10000℃ / s, particle size 50-100μm), hot isostatic pressing (temperature 450-500℃, pressure 100-120MPa), and flame spraying polyether ether ketone (temperature 300-350℃). However, the improved alloy bridge plug still has some shortcomings. First, the compressive strength of 550MPa still cannot cope with the high pressure (greater than 100MPa) of ultra-deep wells, and the base body is prone to micro-cracks under high pressure. Second, the polyether ether ketone time. Third, the residual particle size is 0.6-0.9mm, and the polyether ether ketone residue is 0.5-0.7mm, which needs to be cleaned and processed, increasing the cost. Fourth, the hot isostatic pressing process requires high-pressure equipment (100MPa), the production cycle is long (2-3h / piece), the cost is high, and the scale production is limited. These shortcomings show that the improved bridge plug is still not ideal in the application of ultra-deep wells.

[0006] The composite bridge plug is a research direction in recent years, the base body contains 85-90wt% magnesium and 5-10wt% aluminum, and the surface is embedded with zirconia ceramic particles (particle size 50-100nm, content 5-10wt%), with a hardness of about 200 Vickers hardness. The outside is coated with a polyglycolic acid coating, with a thickness of 10-20μm, and there is no middle groove group design. The bridge plug diameter is 70-130mm, and the length is 150-280mm. In the downhole environment, the magnesium-based alloy corrodes rapidly, the polyglycolic acid coating hydrolyzes, the dissolution time is 5-15d, the rate is 0.3-2.5mm / d, the compressive strength is 450-520MPa, and the sealing pressure is about 75MPa. The preparation process includes vacuum melting, mechanical mixing of zirconia particles, extrusion molding, and arc spraying coating. This technology is widely used in shale gas working conditions, and the shortcomings of the composite bridge plug are more obvious. First, the compressive strength of 450-520MPa makes it difficult to meet the high pressure demand of ultra-deep wells. Second, the zirconia particles enhance the hardness but hinder the uniform corrosion of the magnesium-based alloy, making it difficult to control the dissolution time. Third, the magnesium-based alloy residue particle size is 0.7-1.0mm, and the zirconia particle residue is larger, which needs to be cleaned and processed. Fourth, there is no middle groove group design, relying on the coating for sealing, with a sealing pressure of less than 80MPa, which is prone to leakage. These shortcomings limit its application in complex working conditions.

[0007] Polymer-based bridge plug is developed for shallow well, the base body adopts polylactic acid or polyglycolic acid composite material, fiber reinforced (fiber content 20-30wt%), and the outside is coated with polyether ether ketone coating with thickness of 15-30μm. The bridge plug has a diameter of 60-140mm, a length of 100-200mm, and an internal passage diameter of 8-12mm. In the downhole environment, the polymer base body is decomposed by hydrolysis, the dissolution time is 3-10d, the rate is 0.5-3.0mm / d, the compressive strength is 300-400MPa, and the sealing pressure is about 60MPa. The preparation process comprises injection molding of the base body (temperature 200-250℃, pressure 10-20MPa) and thermal spraying of polyether ether ketone (temperature 280-320℃). The technology is also applied to shale gas wells. The disadvantages of the polymer-based bridge plug are particularly prominent. First, the compressive strength is only 300-400MPa, which is only suitable for shallow wells (pressure less than 60MPa) and cannot withstand high pressure in ultra-deep wells. Second, polylactic acid or polyglycolic acid hydrolyzes too fast at high temperature (greater than 140℃), and the dissolution time is difficult to accurately control, which affects the operation plan. Third, the residual particle size is 0.3-0.8mm, and the fiber reinforced material residue is 0.1-0.5mm, which increases the risk of downhole plugging. Fourth, the adhesion of the polyether ether ketone coating is weak (interfacial strength less than 50MPa), the sealing pressure is less than 60MPa, and it is easy to fail. These deficiencies make it impossible to meet the needs of ultra-deep wells.

[0008] Therefore, the common deficiencies of the existing bridge plug technology in ultra-deep well fracturing include that the compressive strength is generally less than 550MPa, it is difficult to withstand pressure greater than 100MPa; the dissolution time is 7-30d, the rate fluctuates greatly (0.1-3.0mm / d), and it is difficult to accurately control; the residual particle size is greater than 0.8mm, which increases the risk of plugging; the sealing pressure is 60-85MPa, and it is easy to fail in high-temperature acidic environment (140-160℃, pH 3.5-4.5); the traditional casting, extrusion or injection molding process is complex, the production efficiency is low, and the cost is high. SUMMARY

[0009] In view of the above problems in the prior art, the present application provides a high-strength nano-hybrid dissolvable bridge plug, a preparation method and application thereof. The bridge plug has high sealing strength, controllable dissolution time, and can adapt to high-temperature high-salt or acidic environment, and the residual particle size after dissolution is small, which can meet the harsh requirements of ultra-deep well fracturing. Moreover, the bridge plug is prepared by one-step forming process, which significantly reduces the production cost.

[0010] In a first aspect, the present application provides a high-strength nanohybrid dissolvable bridge plug, comprising: a bridge plug body comprising a hollow metal tube, a plurality of annular grooves being formed on the outer surface of the hollow metal tube around the axis of the hollow metal tube; a carbon nitride film intermediate layer being located on the outer surface of the bridge plug body; and a polybenzimidazole / nano-silicon oxide composite film outermost layer being located on the outer surface of the carbon nitride film intermediate layer; the material of the hollow metal tube is a zinc-based alloy, which is composed of the following components in terms of mass percentage: titanium 5-7%, magnesium 2-4%, bismuth 0.5-2%, and the balance being zinc.

[0011] According to the high-strength nanohybrid dissolvable bridge plug of the present application, the material of the hollow metal tube of the bridge plug body is a zinc-based alloy, which contains a zinc-based solid solution and titanium-magnesium-bismuth precipitated phase, and the grain size is 5-10 μm. Titanium refines the grain size and improves the strength through solid solution strengthening and precipitated phase. Magnesium improves the toughness and dissolution uniformity, and reduces crack propagation. Bismuth promotes galvanic corrosion to accelerate dissolution, so that the particle size of the residue is less than 0.15 mm. Specifically, zinc (electrode potential -0.76 V) and bismuth (+0.31 V) form a micro-battery effect (1.07 V of electrode potential difference), which accelerates corrosion. The zinc-based alloy material provides the bridge plug with a tensile strength of 450-500 MPa and a compressive strength of 700-750 MPa, so as to meet the needs of high-pressure cracking (greater than 100 MPa) in ultra-deep wells. Compared with the strength of 400-550 MPa of the bridge plug made of a traditional aluminum-magnesium alloy material and the residue greater than 0.8 mm after dissolution, the zinc-based alloy material improves the strength of the bridge plug by 30-40%, significantly reduces the particle size of the residue after dissolution, and makes the dissolution more uniform. The hollow cavity inside the metal tube balances the internal and external pressure, guides the flow of downhole fluid, assists the positioning of the setting tool, and optimizes the stress distribution. The annular grooves on the surface of the hollow metal tube replace the traditional rubber seal (such as polyglycolic acid and fluororubber), tightly fit with the downhole casing (inner diameter 70-150 mm), and realize mechanical sealing. The sealing pressure of this sealing method is greater than 100 MPa, which is 25% higher than that of the traditional rubber seal, meets the needs of high-pressure cracking in ultra-deep wells, prolongs the service life, and reduces the risk of failure.

[0012] According to the high-strength nanohybrid dissolvable bridge plug of the present application, the carbon nitride film intermediate layer is metallurgically combined with the bridge plug body through plasma sintering, the interfacial bonding strength is greater than 100 MPa, and it plays a dispersion strengthening role. Compared with the traditional ceramic material enhancement (such as zirconia, porosity greater than 10%), the nano-carbon nitride has a low density (about 2.3 g / cm 3), high hardness and compressive strength (hardness greater than 30 GPa, compressive strength greater than 700 MPa), better deformation resistance, stronger chemical stability, and the reticular microporous structure is conducive to increasing the fluid contact area, regulating the dissolution rate of 0.2-1.8 mm / d (140-160℃, 10-20% sodium chloride solution, pH 3.5-6.5), promoting the corrosion reaction, and the decomposition products are gaseous (such as ammonia and carbon dioxide), and the residual particle size is less than 0.15 mm, which is conducive to reducing solid residues.

[0013] The high-strength nanohybrid soluble bridge plug according to the present application is a polybenzimidazole / nano-silicon oxide composite film formed by doping nano-silicon oxide fillers in a polybenzimidazole polymer substrate. The film material can be attached to the surface of the carbon nitride film through a conventional thermal spraying process at a spraying temperature of 300-340℃ and a pressure of 0.3-0.5 MPa, with a bonding strength greater than 50 MPa. It can withstand downhole environmental temperatures of 140-160℃ and acidic conditions of pH 3.5-6.5 while maintaining sealing performance and structural integrity. Specifically, it provides flexible sealing during the initial stage of fracturing operations (6-8h), with a function similar to that of a traditional rubber sealing ring, ensuring a sealing pressure greater than 100 MPa to meet the high-pressure requirements of ultra-deep wells. The nano-silicon oxide enhances the hardness (150-200 Vickers hardness) and corrosion resistance of the composite film, regulating the contact between the downhole acidic medium (such as a 10-20% sodium chloride solution with pH 3.5-6.5) and the composite film, and extending the sealing durability. The composite film achieves controlled dissolution through acid hydrolysis, with a dissolution time of 4-12 days, a rate of 0.2-1.8 mm / d, and a residual particle size of less than 0.15 mm, which is much better than that of traditional polyglycolic acid coatings (residual particles greater than 1 mm) or polyether ether ketone coatings (residual particles 0.5-0.7 mm). In comparison, the polybenzimidazole / nano-silicon oxide composite film has higher thermal stability (greater than 400℃) and more uniform degradation. The degradation principle is that the benzimidazole units of polybenzimidazole degrade through acid hydrolysis in the downhole environment of 140-160℃ and pH 3.5-6.5, generating small molecular products, and the degradation rate is adjusted by the molecular weight of polybenzimidazole and the content of nano-silicon oxide. Nano-silicon oxide catalyzes the hydrolysis reaction through surface hydroxyl groups, reducing the activation energy and enhancing the acid resistance and mechanical strength.

[0014] In some embodiments, the interior of the hollow metal tube is a conical cavity. In other embodiments, the conical cavity has a taper angle of 4-8°, an inlet diameter of 10-14 mm, and an outlet diameter of 6-10 mm. In other embodiments, the hollow metal tube has a diameter of 50-100 mm and a length of 100-200 mm.

[0015] In some embodiments, the annular grooves are located on the outer surface of the middle part of the hollow metal pipe, and the number of the annular grooves is 5-12, such as 5, 6, 8, 10 or 12. In other embodiments, the depth of the annular grooves is 2-4 mm, the width of the annular grooves is 4-8 mm, and the distance between the annular grooves is 8-12 mm. In other embodiments, the distance between the annular grooves and the top and bottom of the hollow metal pipe is 25-70 mm, and the total axial width is 30-150 mm. In other embodiments, the surface roughness Ra of the middle part of the hollow metal pipe is less than 0.25 μm, and the top and bottom are smooth surfaces.

[0016] In some embodiments, the carbon nitride film has a reticular reinforced structure, the porosity is 3-6%, such as 3%, 4%, 5% or 6%; the pore size is 30-80 nm, such as 30 nm, 40 nm, 50 nm, 60 nm, 70 nm or 80 nm; the surface hardness is 250-300 kgf / mm 2 , such as 250 kgf / mm 2 , 260 kgf / mm 2 , 270 kgf / mm 2 , 280 kgf / mm 2 , 290 kgf / mm 2 , 300 kgf / mm 2 . In other embodiments, the carbon nitride film is dispersed on the outer surface of the bridge plug body in the form of single or multiple layers by nano carbon nitride with a particle size of 10-30 nm, the thickness is 0.2-0.5 mm, such as 0.2 mm, 0.3 mm, 0.4 mm or 0.5 mm, and the mass of the carbon nitride film accounts for 1.5-2.5% of the total mass of the surface layer of the bridge plug body.

[0017] In some embodiments, the thickness of the polybenzimidazole / nano-silicon oxide composite film is 8-15 μm, such as 8 μm, 10 μm, 12 μm or 15 μm, and the thickness deviation is less than 1 μm, ensuring uniformity and stability. In other embodiments, the surface roughness Ra of the polybenzimidazole / nano-silicon oxide composite film is less than 0.2 μm, providing a smooth contact surface and reducing fluid resistance. The polybenzimidazole / nano-silicon oxide composite film is combined with the nano-carbon nitride reinforced layer of the surface layer of the bridge plug body by van der Waals force, forming a stable interface structure and enhancing the adhesion and durability.

[0018] In some embodiments, the mass ratio of polybenzimidazole to nano-silicon oxide in the polybenzimidazole / nano-silicon oxide composite film is 80-90:10-20, for example, it can be 80:10, 85:15, 80:20, 90:10, 90:15, or 90:20. Within this range, reducing the content of nano-silicon oxide weakens the catalysis and slows down the degradation, and increasing the content of nano-silicon oxide enhances the catalysis and speeds up the degradation. In other embodiments, the number average molecular weight of polybenzimidazole is 3×10 4 ~4.5×10 4 , for example, it can be 3×10 4 , 4×10 4 , or 4.5×10 4 . In other embodiments, the particle size of nano-silicon oxide is 15-40 nm. When the particle size is 15 nm, the composite film is dense and the medium penetrates slowly; when the particle size is 40 nm, the number of micropores increases and the penetration is fast. In addition, the degradation of the composite film is mainly affected by the pH value (fast at 3.5 and slow at 6.5) and the ion conduction of sodium chloride solution, and has little relation to temperature.

[0019] In a second aspect, the application provides a method for preparing a high-strength nano-hybrid soluble bridge plug, comprising: step 1: preparing a zinc-based alloy powder, the zinc-based alloy consisting of the following components by mass percentage: titanium 5-7%, magnesium 2-4%, bismuth 0.5-2%, and the balance being zinc; step 2: mixing the zinc-based alloy powder with nano-carbon nitride powder, plasma sintering into a solid cylinder in a mold, turning to form a hollow tubular semi-finished product, and forming a plurality of annular grooves around the axis of the hollow tubular semi-finished product on the outer surface of the hollow tubular semi-finished product; and step 3: preparing a slurry containing polybenzimidazole powder and nano-silicon oxide powder, spraying the slurry onto the surface of the hollow tubular semi-finished product, and drying to obtain a high-strength nano-hybrid soluble bridge plug.

[0020] In some embodiments, step 1 comprises: weighing zinc ingots, titanium particles, magnesium ingots and bismuth particles in proportion, heating to 650-720°C in a vacuum induction furnace, holding for 20-30 min, introducing argon with a purity of greater than 99.99% into the furnace to a pressure of 0.05-0.1 MPa, and stirring electromagnetically at 100-200 r / min to form a melt; pouring the melt into an inert gas atomization tower, spraying high-pressure argon through a stainless steel nozzle (pore size 0.5-1.0 mm) to prevent oxidation, nozzle pressure 0.7-0.9 MPa, argon flow rate 20-50 L / min, melt superheating temperature 680-740°C, cooling rate 100-1000°C / s, blowing the melt into droplets by atomization, rapidly cooling the droplets to solidify into powder. The powder is placed on a vibrating screen, and a screen mesh with a pore size of 30-100 μm is used to screen out powder with a particle size of 30-90 μm. The screened powder is placed in a vacuum drying box, the temperature is set to 80-100°C, and the powder is dried for 2-4 h under a vacuum of less than 0.1 Pa, and then sealed and stored after drying. The vacuum melting ensures uniform alloy composition and prevents oxidation; the melt is atomized into droplets by high-pressure argon and rapidly cooled to form micron-sized powder (grain size 5-10 μm), which facilitates subsequent plasma sintering; screening controls the consistency of the particle size, and drying prevents the powder from getting damp.

[0021] In some embodiments, step 2 includes ball milling a mixture of zinc-based alloy powder and nano-carbon nitride powder at a ball-to-material mass ratio of 8:1 to 12:1, at a milling speed of 250 to 450 rpm for 15 to 35 minutes to obtain a mixed powder. The mixed powder is dried at 80 to 100°C under vacuum conditions below 0.1 Pa for 2 to 4 hours, then placed into a mold and sintered in a plasma sintering furnace to form a solid cylinder. The sintering conditions include: evacuating to a pressure below 0.01 Pa, applying an axial pressure of 35 to 45 MPa, heating to 460 to 480°C at a heating rate of 80 to 120°C / min, and holding at this temperature for 8 to 12 minutes. The solid cylinder is clamped on a CNC lathe, a tapered drill bit (taper angle 4 to 8°) is installed, the speed is set to 700 to 1300 rpm, the feed rate is 0.08 to 0.35 mm / rev, and a water-based emulsion is used for cooling to machine the tapered channel. A carbide turning tool (tip radius 0.2-0.4 mm) was replaced with a tool tip. A speed of 500-1100 rpm and a feed rate of 0.04-0.25 mm / rev were set, using a water-based emulsion for cooling. Five to 12 annular grooves were machined in the center. The surface was then polished for 5-10 minutes using a grinding wheel (1800-2200 mesh) or a phosphoric acid-based chemical polishing solution (10-20% wt%) to a surface roughness Ra of less than 0.25 μm. Ball milling ensured uniform dispersion of the nanocarbon nitride (NCN). Plasma sintering formed the NCN in a single step and embedded it in the surface layer. CNC machining ensured geometric accuracy, and polishing enhanced coating adhesion. The sintering temperature of 460-480°C was kept below the melting point of the zinc-based alloy (approximately 600°C) to prevent decomposition of the NCN. A hydraulic pressure plate applied 35-45 MPa of axial pressure to ensure metallurgical bonding.

[0022] In some embodiments, step 3 comprises: mixing polybenzimidazole (PBI) powder, nano-silicon oxide powder and N,N- Dimethylacetamide mixed, ultrasonic treatment (frequency 35-45 kHz, power 150-250 W) for 20-30 min to obtain a stable and uniform slurry. The slurry is uniformly coated on the outer surface of the hollow tubular semi-finished product to form a wet film by means of airless air spraying, blade coating or spin coating. Preferably, pre-baking (10-60 min) is carried out at 60-120℃ to remove low-boiling components; then placed in a vacuum drying environment (absolute pressure ≤1000 Pa, preferably 200-800 Pa) and dried at 80-120℃ for 2-12 h to further remove the solvent and reduce the internal stress; then heat treatment / densification is carried out at a temperature of 200-260℃ for 2-6 h (preferably 220-240℃ for 3-4 h) to promote the formation of a dense continuous PBI film layer. The final coating thickness is 8-15 μm, the surface roughness Ra is about 0.2 μm, and the coating has good denseness and solvent resistance. Among them, ultrasonic mixing helps to uniformly disperse nano-silicon oxide in the high-viscosity system; staged drying and heat treatment can effectively avoid solvent residue and coating cracking. The cured coating has initial flexible sealing capability (68 h), and its dissolution time can be controlled between 4-12 days by adjusting the formula.

[0023] In some embodiments, the mass ratio of the polybenzimidazole powder to the nano-silicon oxide powder in the slurry is 80-90:10-20, for example, it can be 80:10, 85:15, 80:20, 90:10, 90:15, 90:20, and the total mass of the polybenzimidazole powder and the nano-silicon oxide powder accounts for 88-92% of the mass of the slurry, for example, it can be 88%, 89%, 90%, 91%, 92%.

[0024] In some embodiments, the particle size of the nano-carbon nitride is 10-30 nm, for example, it can be 10 nm, 12 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm.

[0025] In some embodiments, the particle size of the nano-silicon oxide is 15-40 nm, for example, it can be 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm.

[0026] In a third aspect, the present application provides a high-strength nano-hybrid soluble bridge plug prepared by the above method.

[0027] In a fourth aspect, the present application provides the use of the above high-strength nano-hybrid soluble bridge plug in the staged fracturing operation in the oil and gas industry.

[0028] The present application has the following advantages: The bridge plug provided by the application has the following characteristics: (1) super high plugging strength: tensile strength 450-500 MPa, compressive strength 700-750 MPa, which is 30-40% higher than that of a traditional aluminum-magnesium alloy bridge plug. The annular groove structure and the polybenzimidazole / nano-silicon oxide composite film coating on the surface thereof provide a sealing pressure close to 100 MPa, which is 25% higher than that of a traditional rubber seal. The plugging reliability of the bridge plug in ultra-deep well high-pressure fracturing operation is ensured, the service life is prolonged, and the failure risk is reduced. (2) Controllable dissolution time: the dissolution time is accurately controllable within 4-12 days, the dissolution rate is 0.2-1.8 mm / d, and the bridge plug is suitable for high-temperature high-salt or acidic environments (140-160 DEG C, 10-20% sodium chloride, pH 3.5-6.5). The dissolution time is shortened by 40-60% compared with the prior art. The efficiency of fracturing operation is improved, the waiting time downhole is reduced, and the operating cost is reduced. (3) Extremely small residual particle size: the residual particle size after dissolution is less than 0.15 mm, which is more than 80% smaller than that of the prior art (more than 0.8 mm). The downhole plugging risk is significantly reduced, no additional cleaning is required, and the operating cost is reduced.

[0029] The preparation method provided by the application forms the base body and the reinforcing layer in one step through plasma sintering, which reduces the process steps by 20-30% compared with traditional casting. The annular groove is machined by numerical control processing, and the coating is coated by thermal spraying, so that the precision and consistency are ensured. The preparation method greatly improves the production efficiency and the stability of product quality, and is suitable for industrial production. DETAILED DESCRIPTION

[0030] To make the objectives, technical solutions and advantages of the embodiments of the application clearer, the technical solutions in the embodiments of the application are clearly and completely described below. Obviously, the described embodiments are some but not all of the embodiments of the application. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the application.

[0031] Embodiment 1: high-strength and fast-dissolution bridge plug 1. Objectives A bridge plug with high compressive strength and a dissolution time of about 6 days is prepared, which is suitable for rapid fracturing operation.

[0032] 2. Shape and structure Base body: cylindrical, diameter 80 mm, length 150 mm, grain size 5-7 μm. Internal conical channel (cone angle 6°, inlet diameter 12 mm, outlet diameter 8 mm). Eight annular grooves (groove depth 3 mm, groove width 6 mm, groove spacing 10 mm, total axial width 80 mm, distance from top and bottom 35 mm each) on the middle outer surface, surface roughness Ra 0.2 μm.

[0033] Reinforced layer: nano-carbon nitride (particle size 10-20 nm) 2.0 wt% (relative to the total mass of the surface layer), embedded in the matrix surface layer 0.3 mm, porosity 4%, pore size 40-60 nm. Network structure, surface hardness 280 Vickers hardness, metallurgical bonding with the matrix, interface strength 120 MPa.

[0034] Coating: polybenzimidazole (molecular weight 3 x 10 4 ) 85 wt%, nano-silicon oxide (particle size 20 nm) 15 wt%, coating thickness 10 μm. Uniformly cover the surface of the matrix and the groove group, roughness Ra 0.15 μm, thickness deviation less than 0.8 μm.

[0035] 3. Preparation process Step 1: Preparation of alloy powder Take high-purity zinc ingot (purity 99.9%) 90 kg, titanium particles (purity 99.8%) 6 kg, magnesium ingot (purity 99.8%) 3.5 kg, bismuth particles (purity 99.9%) 0.5 kg, into the vacuum induction furnace (graphite crucible, capacity 100 kg), vacuum to 0.008 Pa, argon gas (purity 99.99%) to 0.08 MPa, heated to 680 ℃, electromagnetic stirring 150 r / min, 25 min.

[0036] Pour the melt into the inert gas atomization tower, spray argon gas through the stainless steel nozzle (pore size 0.8 mm) (pressure 0.8 MPa, flow rate 30 L / min), melt superheating temperature 720 ℃, cooling rate 500000 ℃ / s, prepare powder with particle size 30-70 μm, dry (90 ℃, vacuum degree 0.08 Pa, 3 h), get alloy powder.

[0037] Step 2: Matrix forming and reinforced layer embedding Take 2 kg of alloy powder, 40 g of nano-carbon nitride powder (particle size 10-20 nm, purity 99.5%), put it in a high-speed planetary ball mill (stainless steel tank, 1 L), add hard alloy grinding balls (ball to material mass ratio 10:1), dry mix 350 r / min, 20 min, dry (90 ℃, vacuum degree 0.08 Pa, 3 h), get mixed powder.

[0038] Coat the inner wall of the high-purity dense graphite mold (inner diameter 80 mm, graphite powder high temperature and high pressure forming) with graphite lubricant, load the mixed powder, compact to 85% of the mold volume. Put it in a plasma sintering furnace, vacuum to 0.008 Pa, hydraulic pressure pad 40 MPa, heated to 470 ℃ (heating rate 100 ℃ / min), 10 min, natural cooling, take out the matrix (diameter 80 mm, length 150 mm).

[0039] A conical channel (cone angle 6°, rotation speed 1000 r / min, feed rate 0.2 mm / rev, water-based emulsion cooling) and eight annular grooves on the central outer surface (groove depth 3 mm, groove width 6 mm, rotation speed 800 r / min, feed rate 0.1 mm / rev) were machined on a CNC lathe and polished to a roughness Ra of 0.2 μm (2000 grit grinding wheel, polishing for 8 min).

[0040] Step 3: Coating Application Weigh 0.85 kg of polybenzimidazole powder (purity 99%) and 0.15 kg of nano-silicon oxide (purity 99.5%), and add N, N -Dimethylacetamide (10 wt%) was ultrasonically dispersed (40 kHz, 200 W, 25 min) to obtain a slurry. The substrate was preheated to 110°C and the slurry was evenly applied to the outer surface of the substrate obtained in step 2 using flameless air spray to form a wet film. The coating was pre-baked at 85°C for 30 min to remove low-boiling components. It was then dried at 90°C for 10 h in a vacuum drying environment (750 Pa) to further remove solvents and reduce internal stress. Heat treatment / densification was then performed at 220°C for 3 h to promote the formation of a dense, continuous PBI film. The final coating had a thickness of 10 μm and a surface roughness Ra of approximately 0.2 μm, demonstrating excellent density and solvent resistance.

[0041] 4. Performance Testing Tested in a high-temperature, high-pressure reactor (150°C, 110 MPa, 15% sodium chloride, pH 4.5) for 6 days, the dissolution rate was 1.2 mm / day. The residue particle size was 0.04 mm (laser scattering method). The compressive strength was 740 MPa (loading rate 0.8 mm / min, 20°C).

[0042] Example 2: Moderate strength moderate dissolution bridge plug 1. Purpose The bridge plug with high compressive strength of about 720 MPa and dissolution time of about 10 days is prepared, which is suitable for conventional ultra-deep wells.

[0043] 2. Shape and structure Substrate: 60 mm diameter, 180 mm length, grain size 6-8 μm. Tapered channel (5° taper angle, 10 mm inlet diameter, 7 mm outlet diameter). Ten annular grooves on the central outer surface (2.5 mm depth, 5 mm width, 9 mm spacing, 90 mm total axial width, 45 mm from top and bottom), roughness Ra 0.22 μm.

[0044] Reinforced layer: nano-carbon nitride (particle size 15-25 nm) 1.8 wt% (relative to the total mass of the surface layer), embedded in the surface layer 0.4 mm, porosity 5%, pore size 50-70 nm. Hardness 270 Vickers hardness, bonding strength 115 MPa.

[0045] Coating: polybenzimidazole (molecular weight 4.5 x 10 4 ) 88 wt%, nano-silicon oxide (particle size 30 nm) 12 wt%, coating thickness 12 μm. Roughness Ra 0.18 μm, thickness deviation less than 0.9 μm.

[0046] 3. Preparation process Step 1: Alloy powder preparation Take 88 kg of zinc ingot, 7 kg of titanium particles, 3 kg of magnesium ingot, and 2 kg of bismuth particles, melt (700 ℃, 0.07 MPa argon, stirring 180 r / min, holding for 22 min), gas atomization (nozzle 0.7 mm, pressure 0.85 MPa, flow rate 35 L / min, superheating temperature 730 ℃, cooling rate 300000 ℃ / s), prepare particle size 40-80 μm powder, dry (85 ℃, 0.09 Pa, 3.5 h), and obtain alloy powder.

[0047] Step 2: Matrix forming and reinforced layer embedding Take 1.5 kg of alloy powder and 27 g of nano-carbon nitride, wet mix (ethanol, 300 r / min, 25 min), dry (85 ℃, 0.09 Pa, 3 h). Fill the mold (inner diameter 60 mm) with powder, sinter (465 ℃, 42 MPa, heating rate 90 ℃ / min, holding for 11 min), process conical channels (rotating speed 900 r / min, feed 0.15 mm / rev) and 10 annular grooves in the middle outer surface (rotating speed 700 r / min, feed 0.08 mm / rev), polish (chemical polishing solution 15 wt%, 7 min, Ra 0.22 μm).

[0048] Step 3: Coating application Take 0.88 kg of polybenzimidazole and 0.12 kg of nano-silicon oxide, add N,N dimethylacetamide (content 10 wt%), ultrasonic dispersion (38 KHz, 180 W, 22 min), and obtain slurry. Use the scraping method to uniformly coat the slurry on the outer surface of the matrix obtained in step 2 to form a wet film. First, pre-dry at 70 ℃ for 15 min to remove low-boiling components; then place in a vacuum drying environment (600 Pa) and dry at 90 ℃ for 11 h to further remove solvents and reduce internal stress; then perform heat treatment / densification at a temperature of 260 ℃ for 6 h to promote the formation of a dense continuous film layer of PBI. It has good denseness and solvent resistance.

[0049] 4. Performance test Test (155 ℃, 105 MPa, 12% sodium chloride, pH 5.0), dissolution 10 d, rate 0.8 mm / d, residue 0.045 mm, compressive strength 720 MPa.

[0050] Example 3 High-strength long-dissolution bridge plug 1. Objectives To prepare a bridge plug with high compressive strength and a dissolution time of about 12 days, suitable for high-strength long-period operations.

[0051] 2. Shape and structure Base: diameter 100 mm, length 200 mm. Conical channel (taper angle 7°, inlet diameter 14 mm, outlet diameter 10 mm), grain size 7~9 μm. 12 annular grooves on the middle outer surface (groove depth 4 mm, groove width 8 mm, groove spacing 12 mm, total axial width 120 mm, 40 mm from the top and bottom), roughness Ra 0.18 μm.

[0052] Reinforced layer: nano-carbon nitride (particle size 20~30 nm) 2.5 wt% (relative to the total mass of the surface layer), embedded in the surface layer 0.5 mm, porosity 3.5%, pore size 60~80 nm. Hardness 290 Vickers hardness, bonding strength 130 MPa.

[0053] Coating: polybenzimidazole (molecular weight 4.5×10 4 ) 90 wt%, nano-silicon oxide (particle size 40 nm) 10 wt%, coating thickness 15 μm. Roughness Ra 0.12 μm, thickness deviation less than 0.7 μm.

[0054] 3. Preparation process Step 1: Powder preparation Weigh zinc ingot 92 kg, titanium particles 5 kg, magnesium ingot 2.5 kg, bismuth particles 0.5 kg, melt (710 ℃, 0.06 MPa argon, stirring 200 r / min, holding 20 min), gas atomization (nozzle 1.0 mm, pressure 0.9 MPa, flow rate 40 L / min, superheating temperature 740 ℃, cooling rate 800000 ℃ / s), prepare particle size 50~90 μm powder, dry (95 ℃, 0.07 Pa, 4 h), get alloy powder.

[0055] Step 2: Base forming and reinforced layer embedding Take 3 kg of alloy powder and 75 g of nano-carbon nitride, dry mix (400 r / min, 30 min), dry (95 ℃, 0.07 Pa, 4 h). The mold (inner diameter 100 mm) is filled with powder, sintered (480 ℃, 45 MPa, heating rate 110 ℃ / min, holding for 12 min), processed into a conical channel (rotating speed 1100 r / min, feeding 0.25 mm / rev) and 12 annular grooves in the middle outer surface (rotating speed 900 r / min, feeding 0.12 mm / rev), and polished (grinding wheel 2200 mesh, 9 min, Ra 0.18 μm).

[0056] Step 3: Coating application Take 1.8 kg of polybenzimidazole and 0.2 kg of nano-silicon oxide, add N,N - dimethylacetamide (content 10 wt%), ultrasonic dispersion (45 KHz, 220 W, 28 min) to obtain a slurry. The slurry is uniformly coated on the outer surface of the substrate obtained in step 2 to form a wet film by spin coating. First, pre-bake at 65 ℃ for 10 min to remove low-boiling components; then place in a vacuum drying environment (300 Pa) and dry at 85 ℃ for 8 h to further remove solvent and reduce internal stress; then perform heat treatment / densification at a temperature of 210 ℃ for 2 h to promote PBI to form a dense continuous film layer. The final coating has good denseness and solvent resistance.

[0057] 4. Performance test Test (160 ℃, 120 MPa, 18% sodium chloride, pH 4.0), dissolution 12 d, rate 0.5 mm / d, residue 0.03 mm, compressive strength 750 MPa.

[0058] The preferred embodiments of the application are described in detail above, but the application is not limited to the specific details of the above-described embodiments. Within the technical concept of the application, various simple modifications can be made to the technical solutions of the application, and these simple modifications all belong to the protection scope of the application.

Claims

1. A high-strength nanohybrid dissolvable bridge plug, characterized in that, The bridge plug comprises: a bridge plug body comprising a hollow metal tube, a plurality of annular grooves being formed on the outer surface of the hollow metal tube around the axis of the hollow metal tube; a carbon nitride film intermediate layer on the outer surface of the bridge plug body; and a polybenzimidazole / nano-silica composite film outermost layer on the outer surface of the carbon nitride film intermediate layer. The hollow metal tube is made of a zinc-based alloy consisting of, by mass percentage, titanium 5-7%, magnesium 2-4%, bismuth 0.5-2%, and the balance being zinc.

2. The high-strength nanohybrid dissolvable bridge plug of claim 1, wherein, The hollow metal tube has a conical cavity inside; and / or the annular grooves are on the outer surface of the middle part of the hollow metal tube; and / or the number of the annular grooves is 5-12.

3. The high-strength nanohybrid resoluble bridge plug according to claim 2, characterized in that, The conical cavity has a taper angle of 4-8°, an inlet diameter of 10-14 mm, and an outlet diameter of 6-10 mm; and / or the annular grooves have a groove depth of 2-4 mm, a groove width of 4-8 mm, and a groove spacing of 8-12 mm.

4. The high-strength nanohybrid resoluble bridge plug of claim 1, wherein, The carbon nitride film has a thickness of 0.2-0.5 mm; and / or the carbon nitride film has a porosity of 3-6% and a pore size of 30-80 nm.

5. The high-strength nanohybrid resoluble bridge plug of claim 1, wherein, The polybenzimidazole / nano-silica composite film has a thickness of 8-15 μm; and / or in the polybenzimidazole / nano-silica composite film, the mass ratio of polybenzimidazole to nano-silica is 80-90:10-20; and / or; the polybenzimidazole has a number average molecular weight of 3 x 10 4 4.5 x 10 4 ; and / or the nano-silica has a particle size of 15-40 nm.

6. A method for preparing high-strength nanohybrid soluble bridging plugging, characterized in that, The preparation method comprises: preparing a zinc-based alloy powder consisting of, by mass percentage, titanium 5-7%, magnesium 2-4%, bismuth 0.5-2%, and the balance being zinc; mixing the zinc-based alloy powder with nano-carbon nitride powder, plasma sintering the mixture into a solid cylinder in a mold, turning the solid cylinder into a hollow tubular semi-finished product, and forming a plurality of annular grooves on the outer surface of the hollow tubular semi-finished product around the axis of the hollow tubular semi-finished product; preparing a slurry containing polybenzimidazole powder and nano-silica powder, spraying the slurry onto the surface of the hollow tubular semi-finished product, and drying to obtain the high-strength nano-hybrid soluble bridge plug.

7. The production method according to claim 6, characterized by, The plasma sintering is performed under vacuum conditions at a pressure of 35-45 MPa and a temperature of 460-480°C for 8-12 min.

8. The preparation method according to claim 6, characterized in that In the slurry, the mass ratio of polybenzimidazole powder to nano-silica powder is 80-90:10-20, and the total mass of the polybenzimidazole powder and the nano-silica powder accounts for 88-92% of the mass of the slurry. and / or the nano-carbon nitride has a particle size of 10-30 nm; and / or the nano-silica has a particle size of 15-40 nm.

9. The high-strength nano-hybrid soluble bridge plug prepared by the method of any one of claims 6-8.

10. Use of the high-strength nano-hybrid soluble bridge plug of any one of claims 1-5 or claim 9 in segmented fracturing operations in the oil and gas industry.

Citation Information

Patent Citations

  • Formation and modification of ceramic nanowires and use thereof in functional materials

    CN114142054A

  • High-performance polyether-ether-ketone composite material as well as preparation method and application thereof

    CN115353712A

  • Soluble bridge plug with surface coating

    CN119712000A

  • Nanocrystalline material layers using cold spray

    WO2005079209A2

  • Composite-type high-temperature proton exchange membrane for fuel cell, preparation method therefor and use thereof

    WO2022057549A1